2019
DOI: 10.1111/jar.12632
|View full text |Cite
|
Sign up to set email alerts
|

The association between employment and the health of people with intellectual disabilities: A systematic review

Abstract: Background There is strong evidence indicating that paid employment is generally good for the physical and mental health of the general population. This systematic review considers the association between employment and the health of people with intellectual disabilities. Methods Studies published from 1990 to 2018 were identified via electronic literature databases, email requests and cross‐citations. Identified studies were reviewed narratively. Results Twelve studies were identified. Studies were generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 61 publications
(108 reference statements)
2
41
0
1
Order By: Relevance
“…The bivariate analysis identified that unemployment was associated with polypharmacy and psychotropic polypharmacy. As our study had only a small number of employed participants, it would be prudent to consider employment and polypharmacy in larger studies, as employment is associated with better well-being and mental health (Butterworth et al 2011;Hergenrather et al 2015;Robertson et al 2019). It is also important to further examine if the presence of Down syndrome is associated with psychotropic polypharmacy in larger studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The bivariate analysis identified that unemployment was associated with polypharmacy and psychotropic polypharmacy. As our study had only a small number of employed participants, it would be prudent to consider employment and polypharmacy in larger studies, as employment is associated with better well-being and mental health (Butterworth et al 2011;Hergenrather et al 2015;Robertson et al 2019). It is also important to further examine if the presence of Down syndrome is associated with psychotropic polypharmacy in larger studies.…”
Section: Discussionmentioning
confidence: 98%
“…2015; Robertson et al . 2019). It is also important to further examine if the presence of Down syndrome is associated with psychotropic polypharmacy in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…As several studies have outlined (Robertson, Hatton, Beyer, Emerson and Baines, 2019;Ellenkamp, Brouwers, Embregts, Joosen and van Weeghel, 2016;Lindstrom, Doren and Miesch, 2011;(Nota, Ginevra and Carrieri, 2010) (ID) having a job is crucial to the personal development of an adult with ID. As finding a workplace is seen as an important milestone in itself, it tends to be the first step towards the beginning of an independent life -as well as a symbol of citizenship and community participation.…”
Section: Ediciones Universidad De Salamanca / CC By-nc-ndmentioning
confidence: 99%
“…More recent policies in disability employment in Australia and internationally, have promoted integrated employment or ‘open employment’, to promote greater financial independence and social inclusion (Beyer et al, 2010; Bond et al, 2001; Wehman et al, 2018). Integrated employment has been found to enhance self‐esteem (Wehman, Inge, Revell, & Brooke, 2007), physical and mental health (Dean et al, 2018; Robertson et al, 2019), independent living skills (Stephens et al, 2005) and quality of life (Beyer et al, 2010; Kober & Eggleton, 2005). However, evidence from Australia as well as the United States and UK shows that the employment of people with intellectual disabilities in integrated settings is on the decline (Butterworth et al, 2015; Riches & MacDonald, 2016).…”
Section: Introductionmentioning
confidence: 99%